2021
DOI: 10.1007/s10796-020-10101-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Data in an Augmented Reality System for Situation Awareness Support in Emergency Control Rooms

Abstract: During crisis situations, emergency operators require fast information access to achieve situation awareness and make the best possible decisions. Augmented reality could be used to visualize the wealth of user-generated content available on social media and enable context-adaptive functions for emergency operators. Although emergency operators agree that social media analytics will be important for their future work, it poses a challenge to filter and visualize large amounts of social media data. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 77 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Situational awareness is the perception, understanding, and prediction of information in the environment during decision-making [16]. Situational awareness is mainly for large or huge dynamic and complex systems with strong uncertainty, and people must intervene in decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Situational awareness is the perception, understanding, and prediction of information in the environment during decision-making [16]. Situational awareness is mainly for large or huge dynamic and complex systems with strong uncertainty, and people must intervene in decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…While specific empirical analyses may precede the development of applications (Reuter et al, 2014;Wulf et al, 2011), our work follows existing studies which have noted the importance of social media for coping with crises and identified related problems of unreliable content and information overload (Comes et al, 2017;Fromm et al, 2021;Tran et al, 2020). We also rely on insights of studies on the spread of misinformation, particularly noting users' needs for an explanation as well as the unsustainability of loweffort interventions (Roozenbeek & van der Linden, 2018;Kirchner & Reuter, 2020;Pennycook et al, 2021).…”
Section: Methodsmentioning
confidence: 78%
“…Our work focuses on targeted social media users and proposes to productively encounter misleading information on social media in a context of high uncertainty, need for transparency and higher risk of information overload (Fromm et al, 2021;Kaufhold et al, 2020). Thereby, we assume users with relatively strong media literacy as well as nonexpert users to interact with information on social media which is reliable to varying degrees (Kahne & Bowyer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…AR has been defined as the term for technologies for augmenting or altering the current reality (Riar et al, 2021), while in VR, all of the sensory information and stimulus of the 'real reality' is rather blocked and inhibited (Manis & Choi, 2019;Yim et al, 2017). Therefore, while VR has been considered as the digital technologies of choice for substituting the perceived reality , AR and VR provide different kinds of experiences to users (Fromm et al, 2021). Regarding AR, the "augmenting" information and content can bring users interactivity, vividness and novelty (McLean & Wilson, 2019;Yim et al, 2017).…”
Section: Extended Realitymentioning
confidence: 99%